The seasonal role of field characteristics on seed-eating bird abundances in agricultural landscapes - Zufiaurre, Emmanuel (2017)
In temperate agroecosystems, avian responses in abundance and distribution to landscape attributes may be exacerbated by the coupling of natural seasons and farming practices. We assessed the seasonal roles of field type, field use in the surroundings, and distance from a field to the nearest woodlot on the abundance of seed-eating birds in a 225,000km2 study area in the Pampas of central Argentina. During spring-summer and autumn of 2011-2013, we randomly selected 392 fields and used transect samples to collect data on abundance and presence of seed-eating bird species. We recorded a total of 11,579 individuals belonging to 15 seed-eating bird species.We used generalized lineal mixed models to relate bird abundance to field type, field use in the surroundings, and distance to the nearest woodlot. In spring-summer (breeding season) most bird responses were associated with their nesting requirements. Species that build their nests in trees, such as eared doves Zenaida auriculata, picazuro pigeons Patagioenas picazuro, and monk parakeets Myiopsitta monachus, were more abundant in fields closer to woodlots, whereas grassland yellow-finches Sicalis luteola, which nest at areas with tall grasses, were more abundant in fields with livestock use patches in the field surroundings. In autumn (non-breeding season), most bird responses were associated with foraging and refuge needs. The high abundance of eared doves in crop stubbles and the association of pigeons at field surroundings dominated by croplands or at crop stubbles surrounded by livestock use fields revealed the intimate association of these species to sites with high availability of food resources. In addition, both picazuro pigeons and spot-winged pigeons Patagioenas maculosa were associated with woodlots, which provide suitable roosting sites. Our results show that in temperate agroecosystems, the relationships between field characteristics and seed-eating bird abundances vary with season.